Risk factors for postoperative sepsis in a neonatal surgical intensive care unit [Yenidoǧan cerrahi yoǧun bakim ünitesinde cerrahi sonrasi sepsis ve risk faktörleri] - (:unkn) unknown (My University, 2002)
Aim: Sepsis remains a significant source of mortality and morbidity in neonatal surgical intensive care units (NSICU). In this retrospective study, we aimed to determine the incidence of postoperative sepsis and to identify the risk factors associated with the development of sepsis in our NSICU. Method: We could reach the files of 72 neonates admitted to our NSICU during the period October 1996 to May 2001. Neonatal postoperative sepsis was defined as growth of microorganism in blood culture, purulent wound discharge or clinical and laboratory data supportive of sepsis in the postoperative period. The neonates having sepsis was named as septic group, the others as control. Eleven probable risk factors were evaluated; sex, prematurity, age at operation, wound type, degree of surgical stress, TPN, having an endotracheal tube, mechanical ventilation, urinary catheterisation, insertion of chest tube and time for. starting postoperative enteral feeding. Results: The postoperative sepsis incidente was 40.21%. Only 18 patients (25%) had positive hemoculture and Klebsiella pneumonia was the most commonly isolated microorganism. Only two cases died due to sepsis. When comparing the septic group with controls, there were no significant difference in sex, prematurity, age at operation and having chest tube. Factors found to be significantly associated with a postoperative sepsis in our NSICU were moderate degree of surgical stress, contaminated wound type, TPN, having an endotracheal tube, mechanical ventilation, urinary catheterisation and time for starting post-operative oral feeding (p<0.001). Conclusion: I. Klebsiella pneumonia was the most common isolated microorganism in our NSICU. 2. The babies undergoing major operation and having a moderate degree of surgical stress were most likely at risk of sepsis. 3. Prolonged TPN, late onset of postoperative enteral feeding and interventive procedures such as having an endotracheal tube, mechanical ventilation, urinary catheterisation were the most frequently encounteced risk factors in our surgical neonates with sepsis.
Keywords: Neonatal surgical intensive care unit; Sepsis